THE EFFECT OF RECITATION METHOD ON HIGH SCHOOL STUDENTS’ SELF-EFFICACY IN EARTHQUAKE PREPAREDNESS - Baskoro Setioputro; Bina Salsabila; Wantiyah Wantiyah; Rismawan Adi Yunanto; Ruris Haristiani (UPT Penerbitan Universitas Jember, 2023)
Background: Earthquake preparedness is the key to preventing potential damage to people who are affected, therefore education about managing earthquake situations is needed. Selfefficacy helps to carry out regular activities with expected results since they’re convinced in their abilities. In this case, the researcher provided education about applying the recitation method to learn about earthquake preparedness. Objective: This study aimed to analyze the effect of the recitation method on earthquake preparedness on high school students’ selfefficacy in Jember. Method: The method used a quasi-experimental design with the nonequivalent control group. The samples were 136 students selected by simple random sampling and divided into an intervention group and a control group. The data were analyzed by T-Test Dependent and Mann Withney. Results: The result showed a p-value of T-Test Dependent in the intervention group was 0.000 (< 0.05) and in the control group was 0.023 (<0.05), hence there was a difference in self-efficacy before and after intervention in the two groups, while Mann Whitney the comparison between the intervention group and control group was 0.047 (< 0.05), so there was a significant difference in self-efficacy between two groups. Conclusion: Based on the result of this study, learning with the recitation method is effective to improve students’ self-efficacy toward earthquake preparedness. Students who are involved in the recitation method are expected to be convinced of their own abilities because they have been through cognitive and motivational processes toward the formation of self-efficacy in earthquake preparedness.